Strategi Pembelajaran Aktif dalam Meningkatkan Motivasi Belajar Peserta Didik pada Mata Pelajaran Fikih - Burhanudin Burhanudin (Lembaga Pengembangan Kinerja Dosen, 2024)
Active learning strategies are considered one of the most effective approaches in creating meaningful, participatory learning processes that enhance students’ intrinsic motivation. In the context of Fiqh learning, the implementation of active learning strategies plays a crucial role because Fiqh not only requires cognitive understanding but also involves strengthening attitudes and internalizing religious values. Traditional teacher-centered learning methods often lead to passive participation, boredom, and a lack of motivation among students. Therefore, the use of active learning strategies—such as group discussions, simulations, problem-solving activities, and experiential learning—can encourage students to participate more actively, think critically, and develop a stronger motivation to achieve better learning outcomes.This study aims to describe how active learning strategies can improve students’ motivation in Fiqh subjects. The analysis shows that engaging students directly in learning activities increases their attention, interest, and sense of responsibility in understanding the material. Additionally, two-way interactions between teachers and students create a more dynamic and enjoyable learning atmosphere. Thus, active learning strategies serve as a relevant and effective approach to enhancing learning motivation and improving the overall quality of Fiqh education.